The Effectiveness Of Mediation As A Non-Litigation Instrument In Reducing Divorce Rates: An Empirical Study In The Religious Court Class 1a Of Gorontalo City - Chinatra Manoppo, Mohammad Raphael; Imran, Suwitno Yutye; Muhtar, Mohamad Hidayat (SM Institute, 2025)
This study aims to evaluate the effectiveness of the role of mediators in reducing divorce rates through mediation mechanisms at the Class 1A Religious Court of Gorontalo City and to identify the main determinants that influence the success or failure of the divorce case resolution process from legal, psychological, and sociocultural aspects. The main problems underlying this study are the high divorce rate handled by the Religious Court every year, as well as the low success rate of mediation even though there is a normative basis in the form of Supreme Court Regulation Number 1 of 2016 which requires mediation efforts in every civil case, including divorce. This condition indicates a gap between the ideality of the law and its implementation in the field. The method used in this study is the empirical legal method with a qualitative approach. Data were obtained through direct interviews with mediator judges, certified mediators, and the parties to the case at the Class 1A Religious Court of Gorontalo City. The results of the study indicate that mediation has significant potential in preventing divorce if carried out seriously and professionally. The success of mediation is largely determined by the capacity and integrity of the mediator, especially in building effective communication, maintaining neutrality, and understanding the emotional aspects of the disputing parties. However, there are a number of inhibiting factors, including the absence of one of the parties in the mediation process, low good faith, lack of certified mediators, and inadequate mediation facilities. Psychological factors such as emotional trauma and unpreparedness to accept compromise are also quite dominant obstacles. In addition, cultural factors such as the public view that still considers the court as an arena for